방송산업에의 경쟁 도입 - 이수일 (한국개발연구원, 2006)
Background and Purpose Traditionally, the competition in the broadcasting industry in Korea has been strictly regulated under the initiative for ‘public interest in broadcasting’, which calls for proper representation of the media, program diversity, and national identity. However, the convergence between the broadcasting and telecommunications sector in terms of technology, service, and business, which has progressed since the early 1990s, has been putting significant competitive pressure on the broadcasting industry. This structural change has put the traditional regulatory structure of the broadcasting industry in question. In addition, the efforts of rebalancing the traditional policy objective o‘f securing public interest of broadcasting’with a newly rising policy objective of‘ enhancing social welfare by introducing or revitalizing competition’have been observed in foreign countries, in particular, the European Union. Reflecting this trend, the report analyzes the market structure and the current competitive situation of free-to-air television market and pay television market. Moreover, the study also investigates whether regulations directly related to the current competition structure of each market can be justified from the perspective of the above mentioned two policy objectives. Finally, this paper offers several policy recommendations to enhance market competition in the broadcasting industry. Main Results Free-to-air TV advertising market in Korea can be characterized as KOBACO (Korea Broadcasting Advertising Corporation) system, in which the total amount of advertising time allowed to free-to-air TV broadcasters must be sold through a monopolistic media representative (i.e. KOBACO) and advertising prices are also regulated by KOBACO. This report analyzes the market structure and competition of three different markets (free-to-air TV advertising market, audience market, and independent TV production market), and shows that competition in all three markets is severely limited by the KOBACO system, in particular, by the price regulation. Then, the report identifies several issues of‘ public interest’thought to be pursued by the KOBACO system and explains that the system has fundamental problems such as a mismatch between regulatory goal and regulatory means in pursuing those public interests. Based on the analysis of the regulatory regime in the free-to-air TV market, this study argues for the dissolution of the KOBACO system and makes an alternative plan for introducing competition into the free-to-air TV advertising market. Three main contents of the alternative plan are as follows: ⅰ) Each free-to-air TV broadcaster should be allowed to choose a way to sell its advertising time, and then each free-to-air TV broadcaster can sell its advertising time by either organizing an internal sales department by setting up a subsidiary media representative, or through an independent media representative; ⅱ) advertising prices should not be determined by regulation but by demand and supply in the free-to-air TV advertising market; and ⅲ) KOBACO needs to continue to act as a media representative for KBS2 and EBS for the next two or three years and thereafter it is desirable to privatize KOBACO. The market structure of pay TV is very different from that of the free-to-air TV in a sense that the function of packaging program contents are in a bundle or a channel. The function of delivering channels to audience are structurally separated in the pay TV market whereas the two functions are internally integrated in the free-to-air market. The former function is performed by program providers (PPs) and the latter is performed by platform operators such as system operators (SOs) in pay TV. There exists a programming distribution market where PPs and platform operators transact channels, which does not exist in the free-to-air TV market. In Korea, most SOs are monopolist